Heat-conducting insulated cable material and preparation method thereof
By dispersing hexagonal boron nitride and spherical boron nitride in polyethylene terephthalate, a thermal conductivity network is constructed, and the problem of insufficient thermal conductivity and insulation of traditional cable materials is solved, and the effect of efficient thermal conductivity and good insulation is achieved.
Patent Information
- Application Number
- CN202411933511.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Traditional cable materials based on polyethylene terephthalate have shortcomings in thermal conductivity and insulation, resulting in heat accumulation, insulation breakdown faults and safety hazards.
By dispersing hexagonal boron nitride and spherical boron nitride in polyethylene terephthalate, a thermal conductivity network is built by using technical means such as esterification reaction and loaded polydopamine to improve the thermal conductivity and insulation properties of the material.
It significantly improves the thermal conductivity and insulation performance of cable materials, effectively prevents local overheating, ensures long-term and stable operation of the cable, and reduces costs.
Smart Images

Figure CN119592024A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable materials, and in particular to a heat-conducting insulating cable material and a preparation method thereof. Background Art
[0002] In today's highly electrified era, cables are key components of power transmission, and their performance directly affects the operating efficiency and safety of the entire power system. Polyethylene terephthalate is often used as the base material of cable materials due to its excellent mechanical strength and corrosion resistance. However, this material has significant defects in thermal conductivity and insulation during actual use.
[0003] Cable materials based on polyethylene terephthalate have a certain insulation resistance and can block some current leakage. However, in actual use, due to the combined influence of daily environmental factors such as temperature changes and electromagnetic interference, its molecular structure will be polarized, causing tiny current channels to gradually form inside the cable material. As time goes by, these tiny channels will gradually expand, and the risk of current leakage will gradually increase, eventually causing insulation breakdown failure, seriously threatening the safe and stable operation of the electrical system.
[0004] Polyethylene terephthalate is a material with low thermal conductivity. When the cable is in operation, heat will inevitably be generated when current passes through it due to the resistance of the cable itself. In some high-power power transmission scenarios, or when the cable is in a densely laid environment, the amount of heat generated will be greater and difficult to dissipate quickly. Due to the poor thermal conductivity of polyethylene terephthalate, heat cannot be effectively conducted away, resulting in heat accumulation inside the cable. This heat accumulation will not only increase the temperature of the cable material itself, but also change the physical and chemical properties of the cable material as the temperature rises. For example, the mechanical strength of the material will decrease as the temperature rises, which may cause the cable to be more easily damaged when subjected to external mechanical stress (such as stretching, bending, etc.). At the same time, the high temperature environment will accelerate the aging process of the cable material, greatly shortening the service life of the cable. In addition, the excessively high temperature inside the cable may also cause some potential safety hazards, such as fire, etc., causing serious losses to the power system.
[0005] CN 109836772 A discloses a heat-conducting cable material, which improves the thermal conductivity of the cable by adding a silane coupling agent to modify carbon nanotubes during the preparation of epoxy resin. The carbon nanotubes themselves have good thermal conductivity and mechanical properties. The phenolic resin is evenly distributed on the surface of the carbon nanotubes and cross-linked and vulcanized. The non-polarity of the carbon nanotubes is increased by this modification. Then, under the action of materials such as styrene-butadiene rubber and zinc oxide, EPDM rubber and carbon nanotubes are cross-linked and cured to form a complex cross-linked network and numerous heat-conducting channels, which significantly improves the thermal conductivity of the cable material. However, tourmaline itself is a mineral material with piezoelectric and thermoelectric properties. When the cable is used, it will introduce additional electric fields or currents inside the material when it is subjected to mechanical stress or temperature changes, which will interfere with the normal electrical properties of the cable and have an adverse effect on insulation. At the same time, carbon fiber also has a high electrical conductivity. If it is unevenly dispersed in the cable material, a local conductive area will be formed, which will further affect the insulation performance of the cable material.
[0006] CN 115458212 A discloses a cable insulating pressure-resistant material and a preparation method thereof, wherein nano-aluminum nitride powder, micron-sized mica powder and micron-sized glass beads are mixed, sintered and ground, and then treated with silane coupling agent KH560 to obtain a composite voltage-stabilizing filler. The composite voltage-stabilizing filler is then mixed with octa-aminophenyl-POSS and added to a prepolymer solution generated by the reaction of p-phenylenediamine and pyromellitic dianhydride to form a stable pressure-resistant layer, thereby improving the insulation of the cable material. However, the cable material has limitations in terms of thermal conductivity, because the mica powder has a flaky structure, although it helps to improve the insulation performance of the material to a certain extent, when heat is transferred along the cable material, it is necessary to bypass the mica layer, which increases the path length of heat conduction and causes a decrease in thermal conductivity. In addition, the glass beads act as a binder and a pore-forming agent in the composite voltage-stabilizing filler, and its internal structure is relatively loose and contains more pores. However, these pores will increase the scattering and obstruction of heat transfer, making it difficult for heat to pass smoothly, just like setting many "traps" on the heat conduction path, seriously affecting the thermal conductivity of the material.
[0007] In summary, in view of the serious deficiencies in thermal conductivity and insulation of traditional cable materials based on polyethylene terephthalate, there is an urgent need to develop a new type of cable material that can have both excellent thermal conductivity and high insulation performance to meet the high performance requirements of modern power systems for cables. Summary of the invention
[0008] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing a heat-conducting insulating cable material.
[0009] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0010] S1. Disperse hexagonal boron nitride in water, add sulfuric acid solution and hydrogen peroxide solution, stir in a constant temperature water bath, cool, centrifuge, dry, add tetraisopropyl titanate, ethylene glycol, antioxidant, terephthalic acid, stir in a constant temperature oil bath, reduce the system pressure and stir, cool in a vacuum environment, and obtain activated polyethylene terephthalate;
[0011] S2, adding spherical boron nitride and dopamine hydrochloride to a Tris-HCl buffer with a pH value of 7.5-8, ultrasonicating, adding amino-terminated polyamidoamine, ultrasonicating at a temperature of 70-80°C, centrifuging, washing with deionized water, and vacuum drying to obtain activated boron nitride;
[0012] S3, mixing activated polyethylene terephthalate and activated boron nitride, stirring, extruding, and cooling to obtain a thermally conductive insulating cable material.
[0013] Preferably, the particle size of hexagonal boron nitride is 10-30 μm.
[0014] Preferably, the weight ratio of hexagonal boron nitride, 98-99% sulfuric acid solution, 30-40% hydrogen peroxide solution, tetraisopropyl titanate, ethylene glycol, antioxidant, terephthalic acid, pyrrole monomer, ferric chloride, and 35-45% sulfuric acid solution is 0.5-1: 0.5-1: 1.5-2.5: 0.03-0.08: 1.2-1.8: 0.01-0.08: 1.8-3: 0.4-1: 1.2-1.8: 5.5-6.5.
[0015] Preferably, in step S1, sulfuric acid solution is added at a rate of 10-20% per minute based on the total weight of the sulfuric acid solution.
[0016] Preferably, in step S1, after the hydrogen peroxide solution is added, the mixture is stirred in a constant temperature water bath, the water bath temperature is 60-70° C., the stirring time is 4-6 h, and the stirring speed is 300-500 r / min.
[0017] Preferably, in step S1, the drying temperature is 70-80°C and the drying time is 8-9h.
[0018] Preferably, in step S1 , the antioxidant is antioxidant 1010 .
[0019] Preferably, in step S1, terephthalic acid is added at a rate of 3-4% per minute based on the total weight of terephthalic acid.
[0020] Preferably, in step S1, after adding terephthalic acid, stirring is performed in a constant temperature oil bath, the oil bath temperature is 220-230° C., the stirring time is 3-4 h, and the stirring speed is 200-300 r / min.
[0021] Preferably, in step S1, the system pressure is reduced to 50-100 Pa by a vacuum pump and stirred for 2-3 h at a stirring speed of 100-200 r / min.
[0022] Preferably, in step S2, the particle size of the spherical boron nitride is 10-50 μm.
[0023] Preferably, in step S2, the weight ratio of spherical boron nitride, dopamine hydrochloride and amino-terminated polyamidoamine is 1-5:1-3:1-2.
[0024] Preferably, in step S3, the stirring time is 0.6-1h, and the stirring speed is 600-700r / min.
[0025] Preferably, in step S3, the extrusion is performed through a twin-screw extruder, the temperature of the plasticizing section is 230-250°C, the temperature of the die head is 230-240°C, the rotation speed is 80-100r / min, and the extrusion speed is 3-5g / min.
[0026] A heat-conducting insulating cable material is made by adopting the preparation method of the heat-conducting insulating cable material.
[0027] Beneficial effects:
[0028] During the synthesis of polyethylene terephthalate, the hydroxylated hexagonal boron nitride treated with sulfuric acid solution and hydrogen peroxide solution undergoes an esterification reaction with the carboxyl group of terephthalic acid, so that the hexagonal boron nitride and the polyethylene terephthalate molecular chain are tightly bound, which greatly limits the movement of electrons between the molecular chains and reduces the electron conduction path, thereby effectively improving the insulation of the material. Hexagonal boron nitride itself has high thermal conductivity. After being chemically bonded to the polyethylene terephthalate molecular chain through the above chemical reaction, a heat conduction channel is formed, and heat can be quickly conducted inside the material along the hexagonal boron nitride, improving the thermal conductivity of the entire material.
[0029] The surface of spherical boron nitride is loaded with polydopamine and then subjected to polyamide amine grafting treatment, which can not only form ion bonds with the carboxyl groups on the activated polyethylene terephthalate chains, with high mutual bonding strength, but also the spherical boron nitride and hexagonal boron nitride jointly construct a three-dimensional thermal conductive structure. Experiments have found that the present invention can greatly improve the thermal conductivity while ensuring the insulation performance of the cable material under high voltage environments.
[0030] In the present invention, hexagonal boron nitride cooperates with spherical boron nitride in a polyethylene terephthalate matrix to form a heat conduction network, forming an efficient heat conduction system in which heat can be smoothly transferred, and the bonding strength between the matrix and the matrix is high, and the light shielding ensures the dispersibility in the system, and a large amount of filling effect can be achieved. Through good bonding with polyethylene terephthalate, it quickly diffuses in the entire cable material, effectively preventing local overheating, and ensuring long-term stable operation of the cable. The cable material preparation method of the present invention is simple, low-cost, and suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a comparison chart of thermal conductivity and thermal diffusion coefficient of the heat-conductive insulating cable materials obtained in Example 5 and Comparative Examples 1-2.
[0032] Figure 2 This is a comparison chart of the volume resistivity of the thermally conductive insulating cable materials obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0033] The present invention will be further explained below in conjunction with specific embodiments.
[0034] The hexagonal boron nitride used below was purchased from Wuhan Kemik Biomedical Technology Co., Ltd., and its particle size is 10-30 μm; the spherical boron nitride used below was purchased from Shandong Pengcheng Ceramic New Materials Technology Co., Ltd., and its particle size is 10-50 μm.
[0035] Example 1
[0036] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0037] S1, 5g of hexagonal boron nitride was dispersed in 50g of water, 5g of 98% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 10% per minute), 15g of 30% hydrogen peroxide solution was added, the mixture was stirred in a 60°C constant temperature water bath for 4h at a stirring rate of 300r / min, cooled, centrifuged, dried at 70°C for 8h, 0.3g of tetraisopropyl titanate, 12g of ethylene glycol, 0.1g of antioxidant 1010 were added, 18g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3% per minute), the mixture was stirred in a 220°C constant temperature oil bath for 3h at a stirring rate of 200r / min, the system pressure was reduced to 50Pa by a vacuum pump and stirred for 2h at a stirring rate of 100r / min, and cooled in a vacuum environment to obtain activated polyethylene terephthalate;
[0038] S2, add 1g of spherical boron nitride and 1g of dopamine hydrochloride to 30g of Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 5min at an ultrasonic frequency of 10kHz, add 1g of amino-terminated polyamidoamine, continue ultrasonicating for 1h at an ultrasonic temperature of 70°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0039] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.6h, and extrude through a twin-screw extruder with a plasticizing section temperature of 230°C, a die head temperature of 230°C, a rotation speed of 80r / min, and an extrusion speed of 3g / min. Cool to obtain a thermally conductive insulating cable material.
[0040] Example 2
[0041] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0042] S1, 10g of hexagonal boron nitride was dispersed in 100g of water, 10g of 99% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 20% per minute), 25g of 40% hydrogen peroxide solution was added, the mixture was stirred in a 70°C constant temperature water bath for 6h at a stirring rate of 500r / min, cooled, centrifuged, dried at 80°C for 9h, 0.8g of tetraisopropyl titanate, 18g of ethylene glycol, 0.8g of antioxidant 1010 were added, 30g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 4% per minute), the mixture was stirred in a 230°C constant temperature oil bath for 4h at a stirring rate of 300r / min, the system pressure was reduced to 100Pa by a vacuum pump and stirred for 3h at a stirring rate of 200r / min, and the mixture was cooled in a vacuum environment to obtain activated polyethylene terephthalate;
[0043] S2, add 5g of spherical boron nitride and 3g of dopamine hydrochloride to 60g of Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 15min at an ultrasonic frequency of 15kHz, add 2g of amino-terminated polyamidoamine, continue ultrasonicate for 2h at an ultrasonic temperature of 80°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0044] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 1 hour at a stirring speed of 700 r / min, extrude through a twin-screw extruder, with a plasticizing section temperature of 250°C, a die head temperature of 240°C, a rotation speed of 100 r / min, an extrusion speed of 5 g / min, and cool to obtain a thermally conductive insulating cable material.
[0045] Example 3
[0046] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0047] S1, 6g of hexagonal boron nitride was dispersed in 60g of water, 6g of 98.2% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 12% per minute), 17g of 32% hydrogen peroxide solution was added, the mixture was stirred in a 62°C constant temperature water bath for 4.5h at a stirring rate of 350r / min, cooled, centrifuged, dried at 72°C for 8.2h, 0.4g of tetraisopropyl titanate, 14g of ethylene glycol, 0.3g of antioxidant 1010 were added, 21g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3.2% per minute), the mixture was stirred in a 222°C constant temperature oil bath for 3.2h at a stirring rate of 220r / min, the system pressure was reduced to 60Pa by a vacuum pump and stirred for 2.2h at a stirring rate of 120r / min, cooled in a vacuum environment, and activated polyethylene terephthalate was obtained;
[0048] S2, add 2g spherical boron nitride and 1.5g dopamine hydrochloride to 40g Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 6min at an ultrasonic frequency of 12kHz, add 1.2g amino-terminated polyamidoamine, continue ultrasonication for 1.5h at an ultrasonic temperature of 72°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0049] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.7h, and extrude through a twin-screw extruder with a plasticizing section temperature of 235°C, a die head temperature of 232°C, a rotation speed of 85r / min, and an extrusion speed of 3.5g / min. Cool to obtain a thermally conductive insulating cable material.
[0050] Example 4
[0051] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0052] S1, 9g of hexagonal boron nitride was dispersed in 90g of water, 9g of 98.8% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 18% per minute), 23g of 38% hydrogen peroxide solution was added, the mixture was stirred in a 68°C constant temperature water bath for 5.5h at a stirring rate of 450r / min, cooled, centrifuged, dried at 78°C for 8.8h, 0.7g of tetraisopropyl titanate, 16g of ethylene glycol, 0.6g of antioxidant 1010 were added, 27g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3.8% per minute), the mixture was stirred in a 228°C constant temperature oil bath for 3.8h at a stirring rate of 280r / min, the system pressure was reduced to 90Pa by a vacuum pump and stirred for 2.8h at a stirring rate of 180r / min, cooled in a vacuum environment, and activated polyethylene terephthalate was obtained;
[0053] S2, add 4g spherical boron nitride and 2.5g dopamine hydrochloride to 50g Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 12min at a frequency of 12kHz, add 1.5g amino-terminated polyamidoamine, continue ultrasonicate for 1.5h at a temperature of 75°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0054] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.9h, and extrude through a twin-screw extruder. The temperature of the plasticizing section is 245°C, the temperature of the die head is 238°C, the rotation speed is 95r / min, and the extrusion speed is 4.5g / min. Cool to obtain a thermally conductive insulating cable material.
[0055] Example 5
[0056] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0057] S1, 7g of hexagonal boron nitride was dispersed in 70g of water, 7g of 98.5% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 15% per minute), 20g of 35% hydrogen peroxide solution was added, the mixture was stirred in a 65°C constant temperature water bath for 5h at a stirring rate of 400r / min, cooled, centrifuged, dried at 75°C for 8.5h, 0.5g of tetraisopropyl titanate, 15g of ethylene glycol, 0.4g of antioxidant 1010 were added, 24g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3.5% per minute), the mixture was stirred in a 225°C constant temperature oil bath for 3.5h at a stirring rate of 250r / min, the system pressure was reduced to 75Pa by a vacuum pump and stirred for 2.5h at a stirring rate of 150r / min, cooled in a vacuum environment to obtain activated polyethylene terephthalate;
[0058] S2, add 3.5g spherical boron nitride and 1.5g dopamine hydrochloride to 50g Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 10min at an ultrasonic frequency of 12kHz, add 1.2g amino-terminated polyamidoamine, continue ultrasonicate for 1.5h at an ultrasonic temperature of 75°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0059] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.8h, and extrude through a twin-screw extruder. The temperature of the plasticizing section is 240°C, the temperature of the die head is 235°C, the rotation speed is 90r / min, the extrusion speed is 4g / min, and the mixture is cooled to obtain a thermally conductive insulating cable material.
[0060] Comparative Example 1
[0061] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0062] S1, 7g of spherical boron nitride was dispersed in 70g of water, 7g of 98.5% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 15% per minute), 20g of 35% hydrogen peroxide solution was added, the mixture was stirred in a 65°C constant temperature water bath for 5h at a stirring rate of 400r / min, cooled, centrifuged, dried at 75°C for 8.5h, 0.5g of tetraisopropyl titanate, 15g of ethylene glycol, 0.4g of antioxidant 1010 were added, 24g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3.5% per minute), the mixture was stirred in a 225°C constant temperature oil bath for 3.5h at a stirring rate of 250r / min, the system pressure was reduced to 75Pa by a vacuum pump and stirred for 2.5h at a stirring rate of 150r / min, and cooled in a vacuum environment to obtain activated polyethylene terephthalate;
[0063] S2, add 3.5g hexagonal boron nitride and 1.5g dopamine hydrochloride to 50g Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 10min at a frequency of 12kHz, add 1.2g amino-terminated polyamidoamine, continue ultrasonicate for 1.5h at a temperature of 75°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0064] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.8h, and extrude through a twin-screw extruder. The temperature of the plasticizing section is 240°C, the temperature of the die head is 235°C, the rotation speed is 90r / min, the extrusion speed is 4g / min, and the mixture is cooled to obtain a thermally conductive insulating cable material.
[0065] Comparative Example 2
[0066] A method for preparing a thermally conductive insulating cable material comprises the following steps:
[0067] S1, 7g of hexagonal boron nitride was dispersed in 70g of water, 7g of 98.5% sulfuric acid solution was added (based on the total weight of the sulfuric acid solution, the sulfuric acid solution was added at a rate of 15% per minute), 20g of 35% hydrogen peroxide solution was added, the mixture was stirred in a 65°C constant temperature water bath for 5h at a stirring rate of 400r / min, cooled, centrifuged, dried at 75°C for 8.5h, 0.5g of tetraisopropyl titanate, 15g of ethylene glycol, 0.4g of antioxidant 1010 were added, 24g of terephthalic acid was added (based on the total weight of terephthalic acid, the terephthalic acid was added at a rate of 3.5% per minute), the mixture was stirred in a 225°C constant temperature oil bath for 3.5h at a stirring rate of 250r / min, the system pressure was reduced to 75Pa by a vacuum pump and stirred for 2.5h at a stirring rate of 150r / min, cooled in a vacuum environment to obtain activated polyethylene terephthalate;
[0068] S2, add 3.5g hexagonal boron nitride and 1.5g dopamine hydrochloride to 50g Tris-HCl buffer with a pH value of 7.5-8, ultrasonicate for 10min at a frequency of 12kHz, add 1.2g amino-terminated polyamidoamine, continue ultrasonicate for 1.5h at a temperature of 75°C, centrifuge, wash with deionized water, and vacuum dry to obtain activated boron nitride;
[0069] S3. Mix activated polyethylene terephthalate and activated boron nitride, stir for 0.8h, and extrude through a twin-screw extruder. The temperature of the plasticizing section is 240°C, the temperature of the die head is 235°C, the rotation speed is 90r / min, the extrusion speed is 4g / min, and the mixture is cooled to obtain a thermally conductive insulating cable material.
[0070] Test Example 1
[0071] The thermal conductivity and thermal diffusion coefficient of the cable materials after treatment in Example 5 and Comparative Examples 1-2 were tested as follows:
[0072] Cut 10×10 mm square samples of the same weight from the cable materials prepared in Example 5, Comparative Example 1 and Comparative Example 2, and ensure that the sample surface is flat, clean and undamaged; use a vernier caliper to measure the size of the cable material sample; place the sample on the sample stage of the laser flash thermal conductivity meter (model: LFA467 HyperFlash), and ensure that the sample is in close contact with the sample stage to avoid air gaps affecting the measurement results. Set appropriate measurement parameters, start the laser flash thermal conductivity meter, emit laser pulses, and after the measurement, the instrument automatically gives the results of thermal conductivity and thermal diffusivity.
[0073] Depend on Figure 1 It can be seen that the thermal conductivity and thermal diffusion coefficient of the cable materials prepared in Example 5 and Comparative Examples 1-2 are ranked as Example 5>Comparative Example 1>Comparative Example 2, that is, the cable material prepared in Example 5 exhibits the best thermal conductivity, which is better than Comparative Examples 1-2 (P<0.05).
[0074] Test Example 2
[0075] The volume resistivity of the cable materials after treatment in Example 5 and Comparative Examples 1-2 was tested as follows:
[0076] Cut 10×10 mm square samples of the same weight from the cable materials prepared in Example 5, Comparative Example 1 and Comparative Example 2, and ensure that the surface of the samples is flat, clean and undamaged; measure the size of the cable material samples with a vernier caliper; place the samples on a flat platform, use a level to ensure that the platform is level, and then slowly place three electrodes (high-voltage electrode, measuring electrode and protective electrode) on the sample, and ensure that the sample is placed flat on the electrodes and is in full contact with the electrodes; set a suitable test voltage and measurement range on a high resistance meter (model: ZC-90F); start the high resistance meter, start measuring, record data, and calculate the volume resistivity result according to the formula.
[0077] Use the following formula to calculate:
[0078] R is the measured resistance value; S is the effective area of the measuring electrode; d is the thickness of the sample.
[0079] Depend on Figure 2 It can be seen that the volume resistivity of the cable material prepared in Example 5 is the highest, showing the best insulation, while Comparative Example 1 is second and Comparative Example 2 is the worst, but there is no significant difference among the three (P>0.05).
[0080] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive insulating cable material, characterized in that: The steps include: S1. Disperse hexagonal boron nitride in water, add sulfuric acid solution and hydrogen peroxide solution, stir in a constant temperature water bath, cool, centrifuge, dry, add tetraisopropyl titanate, ethylene glycol, antioxidant, terephthalic acid, stir in a constant temperature oil bath, reduce the system pressure and stir, cool in a vacuum environment, and obtain activated polyethylene terephthalate; S2, adding spherical boron nitride and dopamine hydrochloride to a Tris-HCl buffer with a pH value of 7.5-8, ultrasonicating, adding amino-terminated polyamidoamine, ultrasonicating at a temperature of 70-80°C, centrifuging, washing with deionized water, and vacuum drying to obtain activated boron nitride; S3, mixing activated polyethylene terephthalate and activated boron nitride, stirring, extruding, and cooling to obtain a thermally conductive insulating cable material.
2. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: The weight ratio of hexagonal boron nitride, 98-99% sulfuric acid solution, 30-40% hydrogen peroxide solution, tetraisopropyl titanate, ethylene glycol, antioxidant, terephthalic acid, pyrrole monomer, ferric chloride and 35-45% sulfuric acid solution is 0.5-1: 0.5-1: 1.5-2.5: 0.03-0.08: 1.2-1.8: 0.01-0.08: 1.8-3: 0.4-1: 1.2-1.8: 5.5-6.
5.
3. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S1, sulfuric acid solution is added, and the speed of adding sulfuric acid solution is 10-20% per minute based on the total weight of the sulfuric acid solution.
4. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S1, after adding the hydrogen peroxide solution, stirring is performed in a constant temperature water bath, the water bath temperature is 60-70° C., the stirring time is 4-6 hours, and the stirring speed is 300-500 r / min.
5. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S1, the drying temperature is 70-80°C and the drying time is 8-9h.
6. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S1, terephthalic acid is added at a rate of 3-4% per minute based on the total weight of the terephthalic acid.
7. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S1, after adding terephthalic acid, stirring is performed in a constant temperature oil bath, the oil bath temperature is 220-230° C., the stirring time is 3-4 hours, and the stirring speed is 200-300 r / min.
8. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S2, the weight ratio of spherical boron nitride, dopamine hydrochloride and amino-terminated polyamidoamine is 1-5:1-3:1-2.
9. The method for preparing the thermally conductive insulating cable material according to claim 1, characterized in that: In step S3, the extruder is used for extrusion, the temperature of the plasticizing section is 230-250° C., the temperature of the die head is 230-240° C., the rotation speed is 80-100 r / min, and the extrusion speed is 3-5 g / min.
10. A thermally conductive insulating cable material, characterized in that: The thermally conductive insulating cable material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Heat-conducting electric cable material
CN109836772A
Special heat-conductive insulating material for new energy automobile battery
CN108659327A
High-thermal-conductivity insulating resin composition, high-thermal-conductivity insulating film and preparation method of high-thermal-conductivity insulating film
CN117986809A
Preparation method of thermal interface material based on multi-component composite high-thermal-conductivity filler
CN118638379A
Modified polyester resin for powder coating and preparation method thereof
CN119019661A